Kontribusi Kecepatan Reaksi Kaki Dan Koordinasi Mata-Kaki Terhadap Keterampilan Menggiring Bola Dalam Permainan Sepakbola PS.Telkom Makassar - Mappaompo, M. Adam (Hanoman Journal: Physical Education and Sport, 2023)
The results of this study show that foot reaction speed contributes to dribbling skills in soccer games by 47.4%, and eye-foot coordination contributes to dribbling in soccer games by 58.7%. Meanwhile, foot reaction speed and eye-foot coordination together contributed significantly to dribbling in football games for PS.Telkom Makassar players by 67.9%. Therefore, to improve dribbling skills in the game of football, you must increase the elements of foot reaction speed and eye-foot coordination, because these two elements simultaneously contribute significantly to dribbling skills in the game of football